Dichapetalum salicinum (Dichapetalaceae), a new narrowly leaved species from Peninsular Malaysia - Rahman, Rafidah Abdul; Lu, Lim Chung; Hassan, Nik Faizu Nik (Phytotaxa, 2025)
A new species of Dichapetalum from Peninsular Malaysia is described. This new species, Dichapetalum salicinum, can easily be recognised by extremely narrow linear-lanceolate leaf lamina less than 2 cm wide in contrast to other species that typically have elliptic, oblong, or ovate leaf lamina. It is known from a single locality in coastal heath forest in Jambu Bongkok, Terengganu. Its conservation status is assessed as Critically Endangered, as the species is under severe threat from fire. An updated key to Dichapetalum in Peninsular Malaysia is provided.